Microparticles: New Protagonists in Pericellular and Intravascular Proteolysis - Lacroix, Romaric; Dignat-George, Francoise (Seminars in Thrombosis and Hemostasis, 2013)
Microparticles (MPs) are small vesicles resulting from the shedding of cellular membrane during activation or apoptosis processes. Beyond their well-described procoagulant property, accumulating data show that specific endothelial cell-, leukocyte-, tumor-derived MPs bind plasminogen and vectorize plasminogen activators, leading to an efficient plasmin generation and matrix metalloproteinases activation. This review focuses on the molecular equipment of MPs subpopulations that identify MPs as efficient support for plasmin generation and the potential consequences of this new function. By the combined facts that MPs may disseminate, concentrate active proteolytic molecules and represent a protective environment against soluble inhibitors, MPs behave as an efficient catalytic surface involved in vascular and matrix proteolysis–related biological processes. The existence of this proteolytic MPs in the circulation or in body fluids raises the question about the physiological relevance of this activity. Consequences are suggested in many biological processes such as fibrinolysis, cell survival, matrix remodeling, angiogenesis, and tumor metastasis. However, further studies will be necessary to determine the extent in which in vivo MPs contribute to these pathophysiological mechanisms and how this circulating property of MPs may represent a new biomarker in specific clinical situations.
Keywords: microparticles; plasmin; matrix metalloproteinases; proteolysis